2018
DOI: 10.3390/polym10080847
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Pressure-Induced Solidification of Polymers

Abstract: Abstract:By using a self-designed pressure-jump apparatus, we investigated the melt solidification behavior in the rapid compression process for poly-ethylene-terephthalate (PET), polyetherether-ketone (PEEK), isotactic polypropylene (iPP), high-density polyethylene (HDPE), and the living polymer sulfur. The experimental results clearly show that crystallization could be inhibited, and some melts were solidified to the full amorphous state for PET, PEEK, and sulfur. Full amorphous PEEK that was 24 mm in diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…When the pressure increase is sufficiently high and rapid, as the pressurization rate rises greater than R 3 , region IV will be reached, where the pure mesophase can be obtained. Actually, for polymers whose melting point increases with increasing pressure, if the increase in pressure is high and rapid enough, the melt would be solidified to the metastable or even amorphous phase because of the sufficient undercooling induced by pressurization, and it coincides well with our other results [43,53,54].…”
Section: Discussionsupporting
confidence: 88%
“…When the pressure increase is sufficiently high and rapid, as the pressurization rate rises greater than R 3 , region IV will be reached, where the pure mesophase can be obtained. Actually, for polymers whose melting point increases with increasing pressure, if the increase in pressure is high and rapid enough, the melt would be solidified to the metastable or even amorphous phase because of the sufficient undercooling induced by pressurization, and it coincides well with our other results [43,53,54].…”
Section: Discussionsupporting
confidence: 88%
“…In numerous research on iPP/CNTs, the common theme focused on was their crystallization behavior under atmospheric pressure [16,17], but less attention was paid to their solidification behavior induced by high pressure, neither is there any report on the effect of pressurization rate on melt solidification. More recently, several studies proved that pressurization is an efficient approach to prepare polymer materials with special performance, such as living polymer sulfur which exhibits exceptional thermodynamic and kinetic stability, glassy polyether-ether-ketone samples possessing excellent friction and considerable stiffness, and the glassy poly (lactic acid) which shows better cold crystallization performance [18,19,20]. Additionally, our recent work indicated the crystal structure and morphology of iPP can be accurately controlled by adjusting pressurization conditions [21], and firstly proved high pressure-annealing can induce meso-γ transformation [22].…”
Section: Introductionmentioning
confidence: 99%
“…These results above have confirmed that pressurization is a novel method to tailor the crystalline structure of iPP. Besides, pressurization process is superior to temperature cooling preparation, because stress equilibrates within the polymer melts faster than thermal equilibration, thus the pressurization treatments can get rid of thermal conductivity of the melts and would produce products with more uniform structure with larger size, and this is especially common for polymers which have low thermal diffusivities [18]. More importantly, pressurization conditions can be precisely controlled using conventional techniques, which has potential values for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cell viability and the mechanical integrity of hydrogels limit its further potential application, such as 3D bioprinting. The GO nanosheets, as the polymer reinforcement, can endow composite materials with high strength and superior ductility 47,48 , but the aggregation of GO nanosheets in polymer solution can cause the decrease of cytocompatibility of hydrogels. Such aggregation could be improved by grafting some molecules, such as DL-dithiothreitol (DTT), the dispersion of GO nanosheets in a polymer network could be also ameliorated, and the related properties could be further improved 49,50 .…”
Section: Intruductionmentioning
confidence: 99%